Treatment of patients with deforming osteosrthrosis of joints using Diamax drug - Korzh, Mykola; Filipenko, Volodymyr; Leontyeva, Frieda; Podgayskaya, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The purpose of the present study was to assess therapeutic efficacy of Diamax drug in patients with deforming osteoarthrosis as well as to reveal adverse responses during its use. The efficacy of the drug was assessed by its influence on the dynamics of indices, which characterize the basic disease intensity: pain syndrome by the visual analogue scale (VAS), functional activity of affected joints by Leken’s index, biochemical blood analysis. In order to analyse the tolerance of the drug, patients’ subjective complaints were registered, indices of their cardiovascular activity were monitored, results of clinical and biochemical blood tests and clinical urinalysis before and 2 months after the beginning of the treatment were taken into account. A positive therapeutic effect of Diamax drug was found out, as it was demonstrated by a reduced intensity of pain syndrome, a better functioning of affected joints, a depressed activity of an inflammatory process in them owing to a reduced concentration of inflammation markers (interleukin 1, glycoproteins, sialic acids). No negative influence of the drug on the state of viscera was detected.